Directional dominance for low IgM and IgA levels. - Clark, P (1981)
A biometrical genetical analysis of IgG, IgM, and IgA levels in 134 sets of twins is reported. High heritabilities, around .8, are found for all three immunoglobulin levels, and possible reasons for lower heritabilities found in family studies are discussed. There is evidence for genetical dominance tending to decrease IgM and IgA levels, but there is no evidence for the importance of family environment although the presence of dominance may make its detection difficult. The causes of covariation in the three measurements are unclear in males but in females appear to be mainly environmental in correlations with IgA and equally genetical and environmental in the IgG-IgM correlation.